PEMIKIRAN AL-SHAUKANI TENTANG HADITS - Badrus, Noer Chalida (Jurnal al Hikmah, 2018)
al-Shauka>ni> is a capable figure out of the mainstream of a madhhab, and is more inclined towards the traditions expressed by the scholars of ahl al-sunnah wa al-jama> 'ah, as al-Bukha>ri>, Muslim, Abu> Da>wud, Tirmidhi>, Nasa>'i, and Ibn Ma>jah. This article tries to unravel his thoughts about hadith, with the limitation that his popular work in the field of hadith is only one, namely Nail al-Aut}a>r Sharh} Muntaqa al-Akhba>r.